BRANDING DAN LABELING SEBAGAI UPAYA STRATEGI PEMASARAN PRODUK UMKM BINAAN DI KOTA MEDAN - Ratih Amelia; Tyus Windi Ayuni; Nasib Nasib (Jurnal Bina Bangsa Ekonomika, 2024)
This study investigates the influence of branding and labelling on the marketing strategy of fostered MSME products in Medan City. This type of research is quantitative research. The population in this study is the number of micro businesses as many as 1,590-business units or equivalent to 92.60% of the total number of fostered MSMEs in Medan City. The sample in this study uses a simple random sampling technique and totals 319 MSME actors who are the sample of this study. The results of the study show that branding has a positive and partially significant influence on the marketing strategy of MSMEs, by increasing brand recognition, consumer trust, product added value, and competitiveness in the market. Labelling has also been proven to have a positive and significant influence, helping to differentiate products from competitors, increase consumer confidence in product quality, and meet applicable regulatory standards. Simultaneously, branding and labelling together have a significant impact on the marketing strategy of MSMEs in Medan City. The implication of this study is the need to focus on managing a strong brand identity and implementing proper labeling as a strategy to increase sales, customer loyalty, and the competitiveness of MSMEs. Advice for Medan MSME players includes training and mentoring in better business strategies, based on market needs analysis, sales data, and competitor strategies to achieve sustainable growth and improve their marketing performance